Students’ first experience with Objective Structured Clinical Examination in a pharmacy school in Indonesia - Susi Ari Kristina, Nuvi Gustriawanto, M. Rifqi Rokhman, Hardika Aditama, Ika Puspita Sari (Journal of Applied Pharmaceutical Science, 2018)
Objectives: The study objective was to determine the effectiveness of the introduction of OSCE and pharmacy students perception regarding OSCE implementation. Methods: A 7-station OSCE was developed and implemented in the 2015-2016 academic year as part of compulsory pharmacy course. The case competencies examined include pharmaceutical skill practices covered clinical skills, compounding skills, and management skills incorporated into communication aspect. A questionnaire containing items on student perception and acceptance on OSCE implementation was administered after all students completed the OSCE. Results: About 224 and 198 students have completed the evaluation of the OSCE as part of their required courses. Class of 2016 performed better than 2015 counterpart in almost stations. The performance on the drug monitoring station across all classes was relatively poor (55% and 69% passed). Students agreed that the OSCE scenario was relevant with real practice, a high degree of learning gained, and high fairness of assessment, consistency performance of simulated patients, yet the level of difficulty associated with performing tasks is very high, and the students felt that the 10 minutes allocated for completing each task was inadequate. Conclusion: Objective structured clinical examinations can be implemented routinely for assessment of students’ clinical skills.
Keywords: Objective standardized clinical examination (OSCE), pharmaceutical care, pharmacy students, assessment, Indonesia.